2018
DOI: 10.1515/chem-2018-0008
|View full text |Cite
|
Sign up to set email alerts
|

Human Health Risk Assessment of Trace Metals in Surface Water Due to Leachate from the Municipal Dumpsite by Pollution Index: A Case Study from Ndawuse River, Abuja, Nigeria

Abstract: The study assessed the level of heavy metals in surface water across Ndawuse River near the dumpsite at Phase 1 District of the Federal Capital Territory (FCT), Abuja, Nigeria. The results indicated that oxygen demand, turbidity and heavy metals were above the standard limits set for drinking water. Multivariate analysis using principal component analysis and hierarchical cluster analysis revealed natural and anthropogenic activities as sources of heavy metal contamination. The estimated non-carcinogenic effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Rao [26] suggested that landfill sites are breeding grounds for many disease-carrying organisms and can impact human health [6]. In addition, studies have indicated that poor waste management can lead to surface and groundwater contamination [27], air pollution [28] soil contamination [29], and health risk [30]. The statistical analysis indicated that households within 250 m-500 m from the landfills faced similar environmental issues such…”
Section: Discussionmentioning
confidence: 99%
“…Rao [26] suggested that landfill sites are breeding grounds for many disease-carrying organisms and can impact human health [6]. In addition, studies have indicated that poor waste management can lead to surface and groundwater contamination [27], air pollution [28] soil contamination [29], and health risk [30]. The statistical analysis indicated that households within 250 m-500 m from the landfills faced similar environmental issues such…”
Section: Discussionmentioning
confidence: 99%
“…CF was adopted to ascertain the extent of soil contamination with heavy metals. CF is expressed; of impact on soil [3,4], water [5][6][7], air [8,9], and not excluding human [10,11]. Waste generated in many urban areas of Nigeria comprises several materials and by-products [12,13] capable of releasing toxic agents such as lead, cadmium, mercury, cobalt, arsenic, and other toxic metals into the environment [14].…”
Section: Contamination Factor (Cf)mentioning
confidence: 99%
“…It is highly recommended to change the disposal of solid waste at high temperatures and anaerobic conditions (Sriram et al 2017;Ryue et al 2020). COD measures the oxygen used to oxidize organic wastes into inorganic constituents (Bhalla et al 2012), quantifying the chemical toxicity and oxidizable toxins (Enitan et al 2018). The measured COD and BOD 5 levels obtained in this study were more than 150 to 500 times higher than the disposal limits of 200 mg/L and 20 mg/L, respectively recommended by (MECA 1993) (Table 5).…”
Section: Cod and Bodmentioning
confidence: 99%